Effects of crude glycerin in feedlot cattle - Parsons, Garrett L. (Kansas State University, 2010)
Two trials were conducted to evaluate the effects of crude glycerin in feedlot cattle. The objectives of this research were to determine the effects of crude glycerin on animal performance, carcass characteristics, ruminal metabolism, and diet digestibility when fed in steam-flaked corn finishing diets. Trial one utilized crossbred heifers (n = 373) fed finishing diets containing 0, 2, 4, 8, 12, or 16% crude glycerin. Feeding heifers crude glycerin at 8% or less of the diet resulted in improvements in body weight gain and feed efficiency. Dry matter intake decreased linearly (P < 0.001) when glycerin was included at increasing levels from 0 to 16%. Average daily gains of heifers fed crude glycerin increased when glycerin was fed at 2, 4, or 8% of diet DM, but reductions in ADG were noted when glycerin increased to 12 or 16% (linear, P = 0.013; quadratic, P = 0.010). Feeding glycerin had a quadratic effect on G:F, and was optimal when fed at 2% of DM (P = 0.46). Hot carcass weights increased when glycerin was fed at 2, 4, and 8% of the diet, but decreases in HCW were observed with 12 and 16% crude glycerin (linear, P = 0.009; quadratic, P = 0.006). Low concentrations of glycerin can be fed without negatively impacting animal performances. Trial two consisted of a 3 × 3 Latin Square and utilized cannulated crossbred steers (n = 9) fed finishing diets containing 0, 2, or 4% crude glycerin. Apparent total tract digestibilities of DM, OM, starch, CP, and crude fat were unaffected by the addition of glycerin at 0, 2, or 4% of cannulated steer diets (linear, P > 0.51). Apparent total tract digestibilities of NDF tended to decrease as glycerin concentrations increased to 2 and 4% (linear, P <0.13). Ruminal pH increased as glycerin concentrations increased (linear, P < 0.05), and concentrations of butyrate and valerate decreased (linear, P < 0.03). Acetate production also tended to decrease when glycerin increased from 0 to 2 or 4% of the diet (linear, P =0.06). Collectively, these results suggest that glycerin may negatively influence fiber digestion.
Keywords: Glycerin; Zilmax; Agriculture, Animal Culture and Nutrition (0475)